1982
DOI: 10.1017/s0022172400071047
|View full text |Cite
|
Sign up to set email alerts
|

Competitive exclusion of salmonellas from the chick caecum using a defined mixture of bacterial isolates from the caecal microflora of an adult bird

Abstract: SummaryColonization of the caeca of newly hatched chicks by Salmonella typhimurium was prevented by oral administration of a mixture of cultures comprising 48 different bacterial strains originating from an adult bird known to be free from salmonellas. The treatment conferred protection to the same degree as that obtained previously with a suspension of adult caecal contents or an undefined anaerobic culture from the same source and was demonstrated in four separate laboratory trials.Examination of the caecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Although, by using the methods we described, we were unable to isolate a strain of Gram-negative facultative anaerobe which was inhibitory for salmonellas when inoculated on its own we found that a mixture of three strains of bacteria, identified as E. coli, produced a profound reduction in the caecal count of S. typhimurium F98, a strain used by ourselves in previous studies (Smith & Tucker, 1975;Smith & Tucker, 1980) and also by other workers (Impey, Mead & George, 1982). Good protection against colonization of the caeca by this strain was also obtained in chickens reared on different diets and in different breeds of chickens, including a commercial broiler breed.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although, by using the methods we described, we were unable to isolate a strain of Gram-negative facultative anaerobe which was inhibitory for salmonellas when inoculated on its own we found that a mixture of three strains of bacteria, identified as E. coli, produced a profound reduction in the caecal count of S. typhimurium F98, a strain used by ourselves in previous studies (Smith & Tucker, 1975;Smith & Tucker, 1980) and also by other workers (Impey, Mead & George, 1982). Good protection against colonization of the caeca by this strain was also obtained in chickens reared on different diets and in different breeds of chickens, including a commercial broiler breed.…”
Section: Discussionmentioning
confidence: 67%
“…This absence of complete protection has also been observed using the system involving pre-treatment with faeces or caecal contents obtained from adult chickens Rantala, 1974;Impey, Mead & George, 1982). It was considered that, since strains of E. coli were being used for pre-treatment, interference of the colonization of these organisms by E. coli strains already in the alimentary tract may have occurred leading to poor establishment of the protective strains.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ideals behind the two Orders are sound, but they require to be more strictly enforced. In addition the development of techniques for competitive exclusion in young birds (Impey, Mead & George, 1982) could be more actively pursued under commercial conditions. This measure may reduce the degree of salmonella carriage in broiler flocks at the time of slaughter.…”
Section: Resultsmentioning
confidence: 99%
“…Very soon after treatment with such material the chicks acquire the same degree of resistance to colonization by salmonella shown by the adult bird (for review see Mead and Impey [8]). To avoid the possibility of inadvertent introduction of avian pathogens with such material, mixtures of pure cultures of the appropriate microorganisms can be used [9].…”
Section: Introductionmentioning
confidence: 99%